Influência da aplicação de ultrassom em desidratação osmótica de carne bovina - Carvalho, Gisandro Reis de [UNESP] (2014)
Brining is an employed process in meat products that allows reducing the amount of water, making them more stable. The combination of brining with others technologies results in greater process efficiency. Nowadays, due to its wide field of action, ultrasound technology has been applied in food industry, where one of its great advantages is the improved process kinetic. Therefore, the present project aims to study the influence of ultrasound application in the osmotic dehydration process. Initially, meat was chemically characterized. The thermophysical properties (density, dynamic viscosity, specific heat and thermal conductivity) of salt solutions were determined experimentally as a function of concentration and temperature. The kinetic of dehydration was determined by an experimental central composite design involving the variables ultrasonic power and sodium chloride concentration. Empirical and semi-empirical models were employed to the physical and thermal properties of sodium chloride solutions modeling and simulation, as well as the experimental dehydration kinetics, obtaining acceptable statistical fitting results. In addition to the osmotic dehydration assisted with ultrasound modeling was applied the stepwise regression method to construct a model that allows evaluate the moisture content as a function of time, salt concentration and ultrasound power within an experimental data range. Thermo-physical properties were similar to those reported in the literature. The density ranged from 1005,2 to 1178,5 kg∙m-3, while the viscosity showed values from 0.536 to 2.198 mPa∙s, these properties were directly proportional to concentration and inversely to temperature. The specific heat varied from 3.312 to 4.011 kJ∙kg-1∙°C-1, while the thermal conductivity showed values from 0.490 from 0.614 W∙m-1∙°C-1, these two properties were inversely proportional to concentration and only the conductivity showed increase in their values ...